2020
DOI: 10.1136/jclinpath-2020-207033
|View full text |Cite
|
Sign up to set email alerts
|

Idylla microsatellite instability assay versus mismatch repair immunohistochemistry: a retrospective comparison in gastric adenocarcinoma

Abstract: Up to 22% of all gastric adenocarcinomas are of the microsatellite instability (MSI) subtype. This subtype may not benefit from conventional adjuvant chemotherapy but does respond to novel immunotherapies. A proportion of MSI gastric adenocarcinomas are associated with inherited disease, inferring an opportunity to screen for further cancers in the patient while also identifying at-risk relatives. Although the importance of MSI subtyping is clear, the methods of detection vary. The main techniques are MSI test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Previous studies using the Idylla MSI test have also reported discrepant results in small subsets of samples screened for dMMR/MSI using different methods, IHC and molecular ones (Idylla and non‐Idylla ones). Interestingly, in about 110 samples with discrepant results between Idylla and non‐Idylla methods, the confrontation to the dMMR/MSI result of a third method confirmed in 60 cases the result of Idylla MSI test whereas false results of this test were concluded in about 50 cases 7,9,11,13–16,18,23 . In some reports, to perform a new Idylla MSI test with another cartridge in case of an initial discrepant result between IHC and Idylla test have also resulted in different molecular results correcting the initial discrepancy 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using the Idylla MSI test have also reported discrepant results in small subsets of samples screened for dMMR/MSI using different methods, IHC and molecular ones (Idylla and non‐Idylla ones). Interestingly, in about 110 samples with discrepant results between Idylla and non‐Idylla methods, the confrontation to the dMMR/MSI result of a third method confirmed in 60 cases the result of Idylla MSI test whereas false results of this test were concluded in about 50 cases 7,9,11,13–16,18,23 . In some reports, to perform a new Idylla MSI test with another cartridge in case of an initial discrepant result between IHC and Idylla test have also resulted in different molecular results correcting the initial discrepancy 13 …”
Section: Discussionmentioning
confidence: 99%
“…5 If IHC is performed routinely in pathology laboratories, molecular analyses can be either outsourced in laboratories with molecular pathology expertise, or, more recently, diagnosed using fully-automated rapid molecular analyses accessible even to pathologists with no expertise in molecular analyses. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The diagnostic strategies combining IHC and MSI molecular testing in the same pathology laboratory are particularly interesting because (1) by avoiding external analyses, they accelerate turnaround times for optimal subsequent treatment choices, (2) they facilitate the in-house close confrontation of the results of these two methods which can be sometimes discrepant due to some features of tumor tissues (e.g., tumor cells versus non-tumor cells contents) and/or non-perfect performances of dMMR/MSI diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Idylla ® MSI assay (Bioartis, NV, Mechelen, Belgium) is a fully-automated PCR-based system that comprises the analysis of seven novel monomorphic homopolymer regions ( ACVR2A , BTBD7 , DIDO1 , MRE11 , RYR3 , SEC31A , SULF2 ) in a single-use cartridge with all reagents on board ( Table 2 ) [ 74 ]. In colorectal, endometrial, and gastric cancers, the Idylla ® system provides a high concordance (>96%) and lower failure rate compared to the standard reference methods [ 75 , 76 , 77 , 78 ]. Less is known about its performance in other cancers and further studies are needed to confirm its interest in such cases [ 79 ].…”
Section: Other Msi Approaches On Tumour Tissue Samplesmentioning
confidence: 99%
“…Generally, the most widely adopted procedure for MSI evaluation relies on the Sanger sequencing-based Bethesda panel, which covers two mononucleotide (BAT-25 and BAT-26) and three dinucleotide (D5S346, D2S123, and D17S250) repetitions [13] or, alternatively, a panel covering five poly-A mononucleotide repeats (BAT-25, BAT-26, NR-21, NR-24, NR-27) [14]. However, recent studies have demonstrated that the fully automated PCR high-resolution melt curve analysis (Idylla TM , Biocartis, Mechelen, Belgium) [11,[15][16][17][18][19][20][21][22][23][24][25][26] and the automated microfluidic electrophoretic run chip-based assay (TapeStation 4200, Agilent Technologies, Santa Clara, CA, USA) are easier to use, faster, and less expensive than Sanger sequencing [11,27,28].…”
Section: Introductionmentioning
confidence: 99%